2000
DOI: 10.1097/00004872-200018050-00009
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α-lipoic acid supplementation lowers blood pressure in spontaneously hypertensive rats

Abstract: Dietary alpha-lipoic acid supplementation in SHRs lowered the systolic blood pressure, cytosolic [Ca2+]i, blood glucose and insulin levels, and tissue aldehyde conjugates, and attenuated adverse renal vascular changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 38 publications
7
129
2
1
Order By: Relevance
“…3,7,27 Several animal studies introduced LA as a blood pressure regulator. [28][29][30][31][32] In a randomized clinical trial, Mazloom and Ansar 33 reported that systolic and diastolic blood pressure significantly improved following 8 weeks of 300 mg LA supplementation in type II diabetes patients. Noori et al 34 observed significant reduction in systolic blood pressure but no change in diastolic blood pressure after 12 weeks of combined administration of LA (800 mg) and pyridoxine (80 mg) in patients with diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,27 Several animal studies introduced LA as a blood pressure regulator. [28][29][30][31][32] In a randomized clinical trial, Mazloom and Ansar 33 reported that systolic and diastolic blood pressure significantly improved following 8 weeks of 300 mg LA supplementation in type II diabetes patients. Noori et al 34 observed significant reduction in systolic blood pressure but no change in diastolic blood pressure after 12 weeks of combined administration of LA (800 mg) and pyridoxine (80 mg) in patients with diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 The treatment with the thiol compound, ␣-lipoic acid (LA) was reported to lower blood pressure in SHR. 16 LA, which is a potent antioxidant (with a redox potential E 0 ϩ of Ϫ290 mV compared with vitamin E, which has a redox potential E 0 ϩ of ϩ370 mV), exists endogenously in tissues and acts as a cofactor of key mitochondrial enzymes, controlling glucose oxidation, such as the pyruvate dehydrogenase and the ␣-ketoglutarate dehydrogenase. 17 In type 2 diabetics, LA treatment was found to increase insulin-stimulated glucose metabolism.…”
Section: Iabetes Is Recognized As An Important Cardiovascular Riskmentioning
confidence: 99%
“…Numerous animal models have shown a key role for oxidative stress (present in the circulation, blood vessels, and kidney) in mediating hypertension [ 56 ]. Ascorbate administration also lowers blood pressure in many hypertensive animal models [58][59][60].…”
Section: An Alternative Hypothesis: the Loss Of Ascorbate And Rise Inmentioning
confidence: 99%
“…Numerous animal models have shown a key role for oxidative stress (present in the circulation, blood vessels, and kidney) in mediating hypertension [ 56 ]. Ascorbate administration also lowers blood pressure in many hypertensive animal models [58][59][60].Epidemiologic studies have confirmed a strong inverse relationship between serum ascorbate levels and blood pressure [61][62][63]. Plasma levels of ascorbate are lower in hypertensive subjects (mean 40 umol/L) compared to normotensive controls (mean 57 umol/L) [ 64 ].…”
mentioning
confidence: 99%